(untitled) (Scientific journal of the Fergana State University, 2024)
The research influence on the kinetics of polymerization and copolymerization of tetrafluoroethylene(TFE) with hexafluoropropylene(HFP) of temperature, the concentration of a low-temperature initiator - diizopropylperoxydicarbonate, the reaction time, the ratio of monomers in the initial mixture, and the presence of organic liquids in the system has been studied. It has been established that with an increase in temperature, initiator concentration and reaction time, the yield of polytetrafluoroethylene (PTFE) and TFE copolymers with HFP increase. It has been shown that PTFE and copolymers of TFE with HFP are resistant to the action of such organic liquids as dimethylformamide, dimethylsulfoxide and etc. at their boiling point. Based on X-ray studies, it was found that with an increase in the content of HFP, the degree of crystallinity of TFE copolymers with HFP decreases. It should be noted that the introduction of HFP units into the composition of the copolymer leads to a slight decrease in its thermal stability.